2011
DOI: 10.1057/kmrp.2011.16
|View full text |Cite
|
Sign up to set email alerts
|

Indicators at the interface: managing policymaker-researcher collaboration

Abstract: The knowledge transfer literature encourages partnerships between researchers and policymakers for the purposes of policy-relevant knowledge creation. Consequently, research findings are more likely to be used by policymakers during policy development. This paper presents a set of practice-based indicators that can be used to manage the collaborative knowledge creation process or assess the performance of a partnership between researchers and policymakers. Indicators for partnership success were developed from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
119
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(124 citation statements)
references
References 34 publications
3
119
1
1
Order By: Relevance
“…Across these models is a common underlying need for sustained partnerships based on the "two-communities" theory [7], which suggests that researchers and users of research (policymakers, managers, practitioners) come from distinct worlds with different cultures, values, timelines, goals and rewards [8]. IKT, or close interactions involving the researcher and research user during knowledge generation and application, is positioned as the bridge across these two worlds [1], leading to: research questions that are more practice or policy relevant; findings that are easier to adapt because they meet a knowledge-practice gap; the creation of a ready audience for implementation strategies; and an increased understanding of each other's roles (and worlds) [2,[9][10][11][12]. Benefits resulting from IKT have also been found to extend beyond the lifetime of the research project [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Across these models is a common underlying need for sustained partnerships based on the "two-communities" theory [7], which suggests that researchers and users of research (policymakers, managers, practitioners) come from distinct worlds with different cultures, values, timelines, goals and rewards [8]. IKT, or close interactions involving the researcher and research user during knowledge generation and application, is positioned as the bridge across these two worlds [1], leading to: research questions that are more practice or policy relevant; findings that are easier to adapt because they meet a knowledge-practice gap; the creation of a ready audience for implementation strategies; and an increased understanding of each other's roles (and worlds) [2,[9][10][11][12]. Benefits resulting from IKT have also been found to extend beyond the lifetime of the research project [11].…”
Section: Introductionmentioning
confidence: 99%
“…IKT, or close interactions involving the researcher and research user during knowledge generation and application, is positioned as the bridge across these two worlds [1], leading to: research questions that are more practice or policy relevant; findings that are easier to adapt because they meet a knowledge-practice gap; the creation of a ready audience for implementation strategies; and an increased understanding of each other's roles (and worlds) [2,[9][10][11][12]. Benefits resulting from IKT have also been found to extend beyond the lifetime of the research project [11]. Effective IKT can be achieved by early engagement of the users in the research process (not just at the dissemination stage [13]); such processes can be supported by financial incentives [12].…”
Section: Introductionmentioning
confidence: 99%
“…Caplan's theory posits that the utilisation of research by policy analysts and decision makers is poor because the assumptions and cultural practices of the two groups differ greatly, so effort is required to bridge the research-policy interface. This assumption is borne out by more recent research that enumerated the characteristics of mature partnerships between knowledge producers and users: trust and openness increases; both parties use a common language regarding research; and the barriers to success on both sides are removed (Kothari et al, 2011). The same research suggested that communication is an important factor in a successful partnership.…”
Section: Introductionmentioning
confidence: 99%
“…We have chosen this approach because of its roots in the 'two communities' theory, because it embraces the social realities of the policy process, and because it offers an ideal framework to develop solutions that complement and support the interactional agenda currently promoted by key government policy documents on innovation. Additionally, it is widely discussed in the academic literature, [9][10][11][12][13][14][15][16][17] promoted by practitioners who work at the research-policy interface, 18,19 and we have direct experience of operationalising this approach. The challenge for knowledge producers is to package one's research for easy policy consumption and to manage the frequent turnover of people within positions.…”
mentioning
confidence: 99%
“…22 Similarly, assessing the success of knowledge brokerage is difficult because of the poor concordance between theoretical models and brokerage in practice. 17 If we hope to improve knowledge exchange at the research-policy interface, we need clearly conceptualised goals, a strong theoretical base, 17 sound performance measures 13 and adequate data. 30 Only then can we assess the veracity of the knowledge-exchange model.…”
mentioning
confidence: 99%